Tulipa toktogulica (Liliaceae), a cryptic, endangered new species from the western Tien-Shan, Kyrgyzstan - Wilson, Brett; Lazkov, Georgy A.; Shalpykov, Kaiyrkul T.; Brockington, Samuel F. (Phytotaxa, 2022)
Tulipa toktogulica (T. sect. Kolpakowskianae; Liliaceae) is a cryptic new species from the Toktogul area of the Jalal-Abad Region, Kyrgyzstan. It is similar to T. talassica, with which it shares the characteristically elongated tunic, but it is genetically and geographically distinct. It has a combination of morphological traits shared between the closely related species T. talassica, T. tetraphylla and T. ferganica, but the combination of its traits is unique. Unlike most other members of the genus, this new species has a scent. It is here also assessed as endangered due to its narrow range and continuing threats from overgrazing.